(untitled) (Mongolian Journal of International Affairs, 2024)
After the establishment of diplomatic relations between the Mongolian People’s Republic and the People’s Republic of China in 1949, the Chinese community in the MPR emerged as a significant link facilitating bilateral relations. The formation and evolution of this community were intricately connected to the establishment and functioning of the Association of Overseas Chinese in Mongolia and its associated institutions. Throughout this process, the political decisions made by both the Mongolian and Chinese governments played a pivotal role. Particularly for the Chinese side, the Chinese community served as a crucial platform for its foreign policy objectives during this period. Additionally, the broader context of the Socialist Bloc also greatly influenced the development trajectory of the Chinese community in the MPR.